Assessment On Sustainability Of Cocoyam For Heavy Metal Removal In Industrial Wastewater - Abdul Jabar, Ahmad Khairil (2016)
Wastewater treatment is an integral part of any industry. For the pharmaceutical sector, the wastewater contains heavy metal elements such as lead, mercury, cadmium and arsenic. Removals of these elements are usually achieved using existing methods such as precipitation, filtration, ion exchange and adsorption. However, these methods are often either costly, require technical expertise, not environmentally friendly or produce by products that are difficult to dispose of and is of no use. A local pharmaceutical company has employed cocoyam as an alternative. Previous study have proven that cocoyam has the ability to adsorb heavy metal elements gradually, until the levels are low enough for ideal conditions of bio indicators such as catfish and koi. It is beneficial to look at the traces of the adsorbed heavy metal in the plant itself, as it would mean that the cocoyam can be used for other purposes such as for human consumption. This would mean that using cocoyam as a wastewater treatment method for removing heavy metals is not only cheap and environmentally friendly, but is also sustainable. Samples of leaf and stalk from the ponds were taken. The tuber, corm and cormet could not be tested as it has not reached 1 year old and according to company directives, could not be dug up. Lab testing on samples were conducted at Central Lab, Universiti Malaysia Pahang. The results were compared to FAO CODEX STAN 193-1995 for safe heavy metal content limit and Provisional Tolerable Weekly Intake (PTWI). It was found that the stalk and leaf can be considered safe for consumption with reservations.